Siberian and Bukhara khanates in the materials of the Kazakh-Russian negotiations of 1595 - Lаpin N.S. (Золотоордынское обозрение)
Research objectives: To consider, on the basis of documentary materials of the Kazakh-Russian embassies in the 1590s, what place in bilateral relations took the issues related to Siberian and Bukhara khanate. Research materials: Materials of research: Archival and published materials of mutual Kazakh and Russian embassies, which were deposited in the Russian State Archive of the Russian Federation in the fund № 122, “Kirghiz-Kaisat affairs”, were used for the study. Results and novelty of the research: The study of the content of the documents of the Kazakh-Russian embassies quite clearly shows the priorities of each party and explains what place in the bilateral relations occupied the Bukhara Khanate headed by Abdallah II and the Siberian state headed by Kuchum. For the Kazakh khan, Tavakkul, who initiated ambassadorial contacts with the Russian kingdom, the main goal was to obtain military assistance from the tsar to fight against Bukhara. At the same time, the issue of “liberation” of the khan’s nephew, Uraz-Muhammed, was not the main one as it is often considered in historiography. For the Russian government, the pressing issue in the eastern direction of foreign policy remained the opposition to Kuchum, in which connection Moscow linked assistance to the Kazakh khanate against Bukhara with reciprocal assistance by the Kazakhs against the Siberian ruler.